PERANCANGAN SISTEM PELAPORAN BBM BERBASIS WEB PADA SPBU KOTA BANJARMASIN - HELDIANSYAH HELDIANSYAH; Muchtar Salim (JURNAL REKAYASA INFORMASI, 2020)
The consumption of the people of Banjarmasin City towards fuel is very high. The transactions served by the gas stations are very much every day. Fuel sales transactions still use manual recording by the management of the Banjarmasin City SPBU. The problems are difficulties in controlling the fuel stock and takes a longer time to make a fuel stock report. This research has developed a fuel reporting system that has a feature that can be accessed at any time with an internet network to make it easier to monitor fuel supplies quickly. The system design using DFD (Data Flow Diagram) begins with the process of requesting fuel to PT Pertamina, selling to the public, and making reports for the head of the gas station. This report is also useful for gas station management in making decisions to determine the number of next fuel orders. Software development uses the method prototype which has the advantage of producing a system that is faster and in accordance with the needs of gas stations. The result of this research is a web-based fuel reporting system that can overcome sales constraints at gas stations in Banjarmasin City. Keywords: Reporting System, Web-based, Fuel, Gas Station